Secondary School Agriculture Curriculum Reforms in Kenya 1959-2016: Challenges to Innovations - Konyango, Jacob J.; Asienyo, Benard O. (Machakos University, 2018)
Fifty seven of curriculum reforms targeting innovations to education through school agriculture remain unattainable to date. Observations indicate challenges to reforms rather progress as there exists a gap between the desired and the reality, the demand for quality and the relevance of what is implemented. The target population for the study included individuals and institutions with both primary and secondary information on innovative strategies on school agriculture. The study used qualitative research with historical design to purposively sample respondents from 26 secondary schools with an initial population of 104 respondents where innovative strategies on school agriculture were implemented. Self-administered interview schedules, visits to school and education offices archives for documentary sources were used to collect data. The data was synthesized and analyzed qualitatively by generating an account of curriculum innovative approaches. This involved selecting, organizing and analyzing the collected data in to topical themes and central ideas and concepts. The findings of this study shows that the perceived reforms either stagnated or were reversed leading to a knowledge and skills gap making the consumers of the curriculum less competitive in the economy of the country. The lessons learnt in this study may help design worthwhile approaches for curriculum reforms with an increased drive for skills and knowledge in producing graduates who are destined to the world of work. The paper recommends the need to establish policy monitoring and implementation machinery to ensure that policies are interpreted and implemented as recommended.
Keywords: Kenya; Reforms; Skills; Curriculum; Strategies; Resources